Identification of NF-κB as Determinant of Posttraumatic Stress Disorder and Its Inhibition by the Chinese Herbal Remedy Free and Easy Wanderer - Hong, Chunlan; Schüffler, Anja; Kauhl, Ulrich; Cao, Jingming; Wu, Ching-Fen; Opatz, Till; Thines, Eckhard; Efferth, Thomas (Frontiers in Pharmacology, 2017)
Posttraumatic stress disorder (PTSD) is a mental disorder developing after exposure to traumatic events. Although psychotherapy reveals some therapeutic effectiveness, clinically sustainable cure is still uncertain. Some Chinese herbal formulae are reported to work well clinically against mental diseases in Asian countries, but the safety and their mode of action are still unclear. In this study, we investigated the mechanisms of Chinese remedy free and easy wanderer (FAEW) on PTSD. We used a reverse pharmacology approach combining clinical data to search for mechanisms of PTSD with subsequent in vitro verification and bioinformatics techniques as follows: (1) by analyzing microarray-based transcriptome-wide mRNA expression profiling of PTSD patients; (2) by investigating the effect of FAEW and the antidepressant control drug fluoxetine on the transcription factor NF-κB using reporter cell assays and western blotting; (3) by performing molecular docking and literature data mining based on phytochemical constituents of FAEW. The results suggest an involvement of inflammatory processes mediated through NF-κB in the progression of PTSD. FAEW was non-cytotoxic in vitro and inhibited NF-κB activity and p65 protein expression. FAEW’s anti-inflammatory compounds, i.e. paeoniflorin, isoliquiritin, isoliquiritin apioside and ononin were evaluated for binding to IκK and p65-RelA in a molecular docking approach. Paeoniflorin, albiflorin, baicalin, isoliquiritin and liquiritin have been reported to relieve depression in vivo or in clinical trials, which might be the active ingredients for FAEW against PTSD.